Profile of residents: attitude towards tourism in Benalmádena (Costa del Sol, Spain) - Almeida-García, Fernando; Cortés-Macías, Rafael; Balbuena-Vázquez, Antonia; Peláez-Fernández, María Ángeles (My University, 2015)
Tourism development and evolution along the time causes multiple impacts. Based on characteristic profiles of resident, these impacts may be assessed differently. The attitude of residents and the identification of profiles is a tool that allows to asses the status of destination and propose future strategies for improving the destination. This study aims to analyse the role of residents regarding the perception of tourism.
Keywords: Turismo - Benalmádena (Málaga); Residents; Attitudes; Tourism; Costa del Sol